Minipterional craniotomy for surgical clipping of anterior circulation aneurysms: compatibility between the feasibility, safety and efficiency - Park, Jung-Sik (J Cerebrovasc Endovasc Neurosurg, 2020)
OBJECTIVE: The aim of this study was to assess the feasibility, safety and efficiency of minipterional craniotomy (MPT) for surgical clipping of anterior circulation aneurysms. METHODS: A retrospective study was conducted to compare the MPT from Jan 2015 to Dec 2018 and conventional pterional craniotomy (CPT) from Jan 2012 to Dec 2013 in unruptured intracranial aneurysms (UIA) and ruptured intracranial aneurysms (RIA). The feasibility and safety of MPT and CPT were assessed by analyzing medical records, radiologic imaging, and clinical outcomes. The efficiency of MPT and CPT were based on a survey research of temporomandibular dysfunction, facial nerve paralysis, and facial asymmetry. RESULTS: Total 628 patients who underwent 458 MPT (UIA:313, RIA:145) and 170 CPT (UIA: 106, RIA: 64) with anterior circulation aneurysms were included in this study. The baseline characteristics between MPT and CPT had no difference (p>0.05). There was no difference in the incidence of postoperative hemorrhage or ischemic lesions between MPT and CPT (p>0.05). The incidence of surgical wound infection was lower in MPT (0.4%) than CPT (3.5%) (p=0.002). More than 90% of postoperative pain disappeared faster in MPT (14.25±4.83 days) than CPT (27.59±10.35 days), and the feeling of facial asymmetry in surgical side was also lower for MPT (1.7%) than CPT (7.6%) (p<0.001). In the MPT, no patients presented with progress to chronic pain, masticatory disability, discomfort of maximal mouth opening or permanent facial palsy. CONCLUSIONS: We suggest that MPT and CPT had similar clinical outcomes, and MPT showed better functional and cosmetic outcomes than CPT in terms of temporomandibular dysfunction, facial nerve paralysis, and facial asymmetry. Therefore, MPT for surgical clipping of anterior circulation aneurysms can be a compatible technique that satisfies the feasibility, safety and efficiency.